Optical tissue clearing in combination with perfusion and immunofluorescence for placental vascular imaging. Issue 39 (September 2018) - Carrillo, Maira; Chuecos, Marcel; Gandhi, Kushal; Bednov, Andrey; Moore, David Lee; Maher, James; Ventolini, Gary; Ji, Guangchen; Schlabritz-Loutsevitch, Natalia
Abstract : Abstract: Imaging of placental tissues is a difficult task, because of specific for this organ complex multicellular and 3D tissue structure. The tissue clearing systems (X-CLARITY) system is a valuable tool for the examining the expression of molecular pathways in whole tissues and organs, originally developed for brain imaging. In the present report, we utilized this technology for the examination of placental vasculature and protein expression in perfused human placental tissue. The placental tissue was sufficiently cleared with preservation of endothelial staining and fluorescent markers, allowing visualization using confocal microscopy. The CLARITY method and X-CLARITY system is a valuable tool in placental imaging. Abstract : Supplemental Digital Content is available in the text